TABOO - Andrew, Brook, 1970-; Museum of Contemporary Art Australia (Sydney, N.S.W.) (The Rocks, NSW : Museum of Contemporary Art Australia, 2013)
Published on the occasion of the exhibition curated by Brook Andrew at the Museum of Contemporary Art Australia, this book presents challenging encounters with a range of artists, both Australian and international, who respond to issues surrounding race, ethnicity, politics and religion. The purposeful breaking of taboos -- crossing the line wherever society forbids it -- is a recurrent impetus for great works of literature and art, and it is the role of artists to precipitate such breaches. With texts by Marcia Langton, Brook Andrew, Fiona McGregor, David Elliott, and others, plus diverse works by artists like Anton Kannemeyer, Maria Kozic, Ken Reinhard and many more.
Includes bibliographical references.
Published for the occasion of the exhibition of the same title at Museum of Contemporary Art Australia, Sydney, on 19 December 2012 - 24 February 2013.
Keywords: Art, Australian -- 21st century -- Exhibitions; Art, Modern -- 21st century -- Exhibitions; Taboo in art; Art - Film; Art - Theory and criticism; Race relations - Attitudes; Art - Conceptual; Art - Postmodernism; Art - Cartoon, comics and caricature; Social organisation - Avoidance rules; Art - Catalogues; Art - Photography; Art - Masks; Art - Objects and installations; Art - Exhibitions; Art - Digital media and technology; Australian